2018
DOI: 10.1177/1074840718755401
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Genetic Risk Information: Implications for Family Nurses Across the Life Span

Abstract: Sharing genetic risk information in families can be very challenging. However, the consequences of poor communication can be detrimental to the psychological health and well-being of parents and children in the present and the long term. Family nursing can play an important role in supporting family communication about genetic conditions. This role has several components: Firstly, improved assessment of families affected by or at risk from inherited genetic conditions. Secondly, facilitation of families' discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…A multidisciplinary approach to genomic medicine has been proposed to be effective in tackling the challenge of disclosure 28 41. GHPs are currently supporting young at-risk relatives within high-risk clinics in Australia, but can also potentially allow for ongoing support of families struggling with disclosure difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…A multidisciplinary approach to genomic medicine has been proposed to be effective in tackling the challenge of disclosure 28 41. GHPs are currently supporting young at-risk relatives within high-risk clinics in Australia, but can also potentially allow for ongoing support of families struggling with disclosure difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Actions included personal risk management through screening, information gathering, and surgical risk reduction, reducing the medical and emotional risks experienced by loved ones, and preserving important relationships. Clinicians working with families at risk of HBOC can apply these findings when providing test results to and counseling family members, to support and leverage naturally communication networks in families (Metcalfe, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Women in this study identified health care providers and other nonfamilial social network members as key providers of information and resources, and brought this new information back to the family to create new potential paths to health for themselves and other at-risk family members. While naturally occurring social networks can provide essential social and emotional support, those incorporating input from experts and extra-familial others expand information available to those at risk (Griffiths et al, 2012; Metcalfe, 2018). Nurses and other health care providers can recognize the importance of the information they provide to women at risk, and ensure that they have up-to-date information on health risks and treatment opportunities to share with at-risk women and others in their families.…”
Section: Discussionmentioning
confidence: 99%
“…When an inherited condition is discovered that definitively leads to disease, discussions about how to share this news with family members can be complex especially if family members have expressed a preference not to be told the results of testing (Metcalfe, 2018). However, discovery of inherited risk for disease is also an opportunity to promote health and prevent disease with the potential for improved health for multiple individuals (Skirton, 2017).…”
Section: Navigating Health Decisions With Familiesmentioning
confidence: 99%
“…Nurses can use their expertise in relational communication to help patients navigate challenging decisions emerging from genetic testing results. Understanding precision health in the context of families means optimizing the health of all family members by helping families navigate difficult conversations, adapt to living with a genetic condition, and cope with psychological challenges (Metcalfe, 2018). Family is defined not only by DNA; however, in the context of genetics and precision health of an individual, it is important to consider the potential benefits and challenges that an individual's genetic information has for their family members.…”
Section: Navigating Health Decisions With Familiesmentioning
confidence: 99%